The right time to change a logo - an extreme case of a parcel delivery company - Vardar, Nükhet (Henry Stewart Talks, 2020)
Logos and their importance to branding, Most common ‘do’s and don’ts’ in logo changes, The power of an existing logo, The case of Yurtici Kargo